Purification, crystallization and structural elucidation of D‐galactaro‐1, 4‐lactone cycloisomerase from Agrobacterium tumefaciens involved in pectin degradation. Issue 1 (1st January 2016) - Vetting, Matthew W.; Bouvier, Jason T.; Gerlt, John A.; Almo, Steven C.
Abstract : Pectin is found in the cell wall of plants and is often discarded as waste. A number of research groups are interested in redirecting this biomass waste stream for the production of fuel and bulk chemicals. The primary monomeric subunit of this polysaccharide is D‐galacturonate, a six‐carbon acid sugar that is degraded in a five‐step pathway to central metabolic intermediates by some bacteria, including Agrobacterium tumefaciens . In the third step of the pathway, D‐galactaro‐1, 4‐lactone is converted to 2‐keto‐3‐deoxy‐L‐ threo ‐hexarate by a member of the mandelate racemase subgroup of the enolase superfamily with a novel activity for the superfamily. The 1.6 Å resolution structure of this enzyme was determined, revealing an overall modified (β/α)7 β TIM‐barrel domain, a hallmark of the superfamily. D‐Galactaro‐1, 4‐lactone was manually docked into the active site located at the interface between the N‐terminal lid domain and the C‐terminal barrel domain. On the basis of the position of the lactone in the active site, Lys166 is predicted to be the active‐site base responsible for abstraction of the α proton. His296 on the opposite side of the active site is predicted to be the general acid that donates a proton to the β carbon as the lactone ring opens. The lactone ring appears to be oriented within the active site by stacking interactions with Trp298.